In-situ X-ray diffraction study of hydrogen-induced phase transformation in wire-feed electron-beam additive manufactured Ti-6Al-4V alloy; Journal of Alloys and Compounds; Vol. 1045 - Kamelina K. D. Kristina Dmitrievna; Panin A. V. Alexey Viktorovich; Syrtanov M. S. Maksim Sergeevich; Kashkarov E. B. Egor Borisovich (2025, 2025)
In situ X-ray diffraction studies of Ti-6Al-4V titanium alloy samples obtained by casting and wire electron beam additive manufacturing (EBAM) are carried out during heating to 450°C and subsequent gas-phase hydrogenation. A different behavior of decreasing the residual stresses, micro-distortions, and increasing the lattice parameters of the α- and β-phases of the cast and EBAM samples demonstrates during heating to 450 °C. The hydrogen content in the cast sample hydrogenated at 450 °C for 55 min does not exceed 0.03 wt%, whereas it reaches 3.4 wt% in the EBAM sample under the same conditions. The XRD establishes that the following phase transformations occur in the process of hydrogenation of the EBAM Ti-6Al-4V sample: α+ β → α+ β+ α" → α+ β+ α"+ort → β+ α''+ort → β +ort+cub → β+cub, where ort is TiH0.71, cub is TiH2. Transmission electron microscopy shows the regularities of hydride phase formation in hydrogenated EBAM sample